Profile of patients with acute pancreatitis undergoing antibiotic prescription in Brazil - Thaynara Karoline de Souza Pereira; Marianges Zadrozny Gouvêa da Costa; George Ramos Lemos (Annals of Pancreatic Disorders and Treatment - Peertechz Publications, 2022)
Approximately 5 to 10% of patients with Acute Pancreatitis (AP) develop necrosis and about 30% of these patients develop an infection, more than doubling the risk of mortality. The treatment of AP has undergone a major revolution in recent decades and recent studies advocate minimally invasive procedures and are based on antibiotic therapy. Underuse of antibiotics can lead to inappropriate treatment, while overuse encourages the emergence of resistant bacterial flora. With the objective to evaluate the profile of patients undergoing antibiotic prescription for acute pancreatitis, the authors carried out a retrospective cross-sectional study in a private hospital in Florianópolis, Brazil. Data collection took place through medical records and the variables were analyzed using simple and relative frequency, measures of central tendency, and their respective measures of variability/dispersion and standard deviation. The present study meets the bioethical principles determined by resolution 466/12 of the National Health Council. Of 91 included patients with acute pancreatitis, 38 (41,7%) received antibiotic therapy. Most were female (58,3%), aged between 40 and 59 years (41,7%). Patients that received antibiotics had more frequently severe presentations according to the Atlanta Revised Classification Criteria (47.4%); of those, in 13 (72.2%) the indication occurred in the presence of pancreatic necrosis or collections. A wide range of antibiotics was used, with Meropenem being the most prescribed (39.5%), followed by the combination of Ampicillin with Sulbactam (28.9%). Positive cultures showed carbapenem-resistant Klebsiella pneumoniae and Pseudomonas aeruginosa in 27,3% of those with positive cultures. The authors conclude that clinical presentation was more severe in cases where there was a need to use antimicrobials. Antibiotics are essential components in the treatment of patients with infection associated with acute pancreatitis and the employment of management protocols that take into account the resistance profile of the local flora is important.